EFFICACY OF LOW DOSE MAGNESIUM SULPHATE REGIME FOR ECLAMPSIA AND IMMINENT ECLAMPSIA: A PROSPECTIVE STUDY - Dr. Sanjay Kumar Patil, Dr. R P Patange, Dr. Yamini Patil (International Journal of Advanced Science and Technology, 2020)
Background: Eclampsia is one of the most serious complications of pregnancy Magnesium Sulphate (MgSo4) is an anticonvulsant of choice for management and prevention of eclampsia.However, its dose linked toxicity is a major concern.